The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1186/s43042-021-00167-8
|View full text |Cite
|
Sign up to set email alerts
|

Role of engulfment and cell motility 1 (ELMO1) gene polymorphism in development of diabetic kidney disease

Abstract: Background Diabetic kidney disease (DKD) is a progressive kidney disease that affects diabetic patients irrespective of glycemic state or hypertension. Therefore, early detection of DKD is of critical importance. Many genome-wide association studies have identified the engulfment and cell motility 1 (ELMO1) gene as a genetic marker linked to DKD. This study aimed to investigate the association between ELMO1 rs741301 gene polymorphism and the development of DKD among Egyptian patients with type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
(45 reference statements)
1
5
0
Order By: Relevance
“…Serum level of VEGF-A was significantly increased in T2DM patients with mixed microvascular complications in comparison with the control group. This result was confirmed by Mahdy et al [25] who found a considerable rise in serum VEGF in diabetic patients with various micro-and macrovascular complications compared to the uncomplicated diabetic patients and control subjects. Biswas et al [26] discovered that elevated VEGF-A level was a risk factor for the presence and severity of vascular complications in diabetic patients, and VEGF-A concentrations tend to increase with the progression of mixed diabetic microvascular complications.…”
Section: Parameterssupporting
confidence: 68%
“…Serum level of VEGF-A was significantly increased in T2DM patients with mixed microvascular complications in comparison with the control group. This result was confirmed by Mahdy et al [25] who found a considerable rise in serum VEGF in diabetic patients with various micro-and macrovascular complications compared to the uncomplicated diabetic patients and control subjects. Biswas et al [26] discovered that elevated VEGF-A level was a risk factor for the presence and severity of vascular complications in diabetic patients, and VEGF-A concentrations tend to increase with the progression of mixed diabetic microvascular complications.…”
Section: Parameterssupporting
confidence: 68%
“…This systematic review finally included 17 studies, of which 15 studies were eligible and included in meta-analysis and the other two studies were excluded due to lack of data (Fig 1). Twelve studies followed a case-control design [4,11,[25][26][27][28][29][30][31][32][33][34] while the other 5 were genomewide association studies [7,[35][36][37][38], with a total of 5794 DM with DKD patients, 4886 DM without DKD patients, and 2023 healthy controls to assess the impact of ELMO1 polymorphism on DKD susceptibility. Most studies included patients with T2DM, except for two studies with T1DM patients [7,36].…”
Section: Study Characteristics and Demographymentioning
confidence: 99%
“…Studies were sub-grouped based on their geographical region; Middle East [25,28,29,32,37], South Asia [26,31,33,35], East Asia [4,11,30,33,38], Europe [34], and USA [7,27,36].…”
Section: Study Characteristics and Demographymentioning
confidence: 99%
See 1 more Smart Citation
“…Higher expression of this protein was suggested to result in aberrant regulation of the extracellular matrix and consequently lead to kidney damage [96]. Another study demonstrated the association between increased expression of ELMO1 and the enhanced production of extracellular protein, diminished cell adhesion, as well as the accelerated progression of T2DM glomerulosclerosis [97]. FKBP5 encodes a cytosolic chaperone FK506 binding protein 51 (FKBP5), which acts as a negative regulator of GR signaling [98].…”
Section: Othermentioning
confidence: 99%